Experimental study of a fixed OWC-type wave energy converter in irregular wave conditions - Nicholas Ulm; Zhenhua Huang; Patrick Cross (Scientific Reports)
Abstract The experimental study of oscillating water column (OWC)-type wave energy converters (WECs) usually focuses on the performance of a WEC in regular wave conditions, as a function of available testing resources. This study examines the power performance of a fixed-geometry OWC that consists of a cylindrical OWC chamber affixed above a plate with V-shaped channels in irregular wave conditions. In evaluating power performance, different representative power take-off (PTO) damping values are considered. Using the data collected from a set of large-scale wave-basin tests, characterizing the quadratic damper relationship in regular and irregular wave conditions is examined, and the method using pressure as the sole measurement to calculate power extraction in irregular waves is assessed. Based on the observation of previous studies of OWCs in regular waves that the power extraction efficiency is not very sensitive to changes in wave amplitude if the wave period is fixed, a method is proposed to estimate the power performance of an OWC-type WEC in irregular wave conditions using results in frequency domain obtained in regular wave conditions. The method was verified using the data presented in this study and the data in the literature for the same WEC in regular wave conditions. The proposed method allows as OWC-type WEC designer to estimate the power extraction of an OWC-type WEC in irregular wave conditions using either experimental or numerical results in frequency domain obtained in regular wave conditions.